IMPLEMENTASI PROGRAM KHITOBAH TERHADAP KEPERCAYAAN DIRI SANTRI PONDOK PESANTREN KYAI HAJI AQIL SIROJ KEMPEK CIREBON - Moh. Hamdan Baihaqi; Nawwal Fayyadah (Walada: Journal of Primary Education, 2023)
Satu paragraf tidak lebih Khithobah is a speech delivered to show listeners the importance of a discussion. Speech is termed khithabah. The Khithobah program is intended to educate students to be skilled and able to speak in front of the audience to convey Islamic teachings in public with confidence. Self-confidence is the ability to be yourself and go anywhere and try anything in a positive sense without feeling afraid or embarrassed. Based on this, it can be formulated how the khithobah program activities at the KHAS Kempek Cirebon Islamic Boarding School take place, how the self-confidence of students at the KHAS Kempek Cirebon Islamic Boarding School, and how the influence of the Khithobah Program in shaping the self-confidence of students at the KHAS Kempek Cirebon Islamic Boarding School. khitobah program activities at the KHAS Kempek Islamic Boarding School are held every Thursday night Friday. The implementation of khitobah activities begins with the opening, recitation of the holy verses of the Qur'an, recitation of the Prophet's sholawat, remarks, delivery of material and the last one is closed with prayer. The Khitobah Program activities carried out at the KHAS Kempek Islamic Boarding School have an effect on the lives of students, namely shaping students' self-confidence, adding new insights for students, and honing students' abilities when speaking in public.